DISPERSION OF SO2 AND NO2 EMITTED BY AUXILIARY BOILER OF PT KMI METHANOL INDUSTRIAL USING THE GAUSSIAN PLUM MODEL AERMOD IN BONTANG CITY EAST KALIMANTAN INDONESIA - Edhi Sarwono; Eka Wijayanto; Hairul Huda; Reynaldi Ferdhani Harrits; Iqbal Fathur Zain (Universitas Mulawarman, 2022)
The petrochemical industry PT Kaltim Methanol Industri Bontang City, uses auxiliary boilers with natural gas fuel and is connected to the stack to emit pollutants into the atmosphere. The objectives of this study are SO2 modeling with a radius of 5 kilometers and modeling of NO2 with a radius of 10 kilometers from the emission source. Modeling using AERMOD software, AERMET Software, and Aermap ArcGIS Software. The wind rose in the dominant research area from the southwest and northeast directions. Dispersion of SO2 and NO2 decreases according to the distance. The increase in concentration occurred in areas that experienced elevation increases, in Teluk Pandan District with a distance of about 10 kilometers northwest with an elevation of about 100 meters above sea level, and part of the West Bontang District with a distance of about 5 kilometers to the southwest with an elevation of about 90 meters above sea level. The maximum concentration of SO2 at the receptor was 6.2631 μg/m3 on hourly modeling, 0.58132 μg/m3 on modeling per 24 hours, and 0.0317 μg/m3 on annual modeling. The maximum NO2 concentration at the receptor was 1.96781 μg/m3 on hourly modeling, 0.18089 μg/m3 on hourly modeling, and 0.01002 μg/m3 on annual modeling. The distribution of pollutants based on hourly modeling per 24 hours is spreading in all directions and irregularly while for annual modeling it tends to spread towards the southwest and northeast according to the wind rose.Keywords: AERMOD, Emissions, Modeling, Air Dispersion, Auxiliary boiler